Oxidation of styrene with hydrogen peroxide over Cu/SBA-15 catalyst - Thao, Nguyen Tien; Thien, Bui The; Hien, Pham Thi; Nhu, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
SBA-15 type silica was loaded with different amounts of copper species prepared via the isothermal treatment method. The obtained solids were characterized by XRD, BET, SEM, TEM techniques. All samples are mesoporous structure, large surface area, uniform pore size, good dispersion of copper species. All Cu/SBA-15 materials exhibited high activity in catalyzing the liquid phase oxidation of styrene with H2O2 solution. The conversion of styrene is about 10-40% with high selectivity to benzaldehyde. Thus, the high catalytic activity for these Cu/SBA-15 catalysts can be attributed to high dispersion of the active sites throughout the support. Keywords. Benzaldehyde, styrene, SBA-15, copper, oxidation.